Strength of Lightweight Cellular Concrete-Filled Hollow Section Added Steel Fiber - Ahmad Hazim Bin Ahmad Firdaus,; Abd Rahman, Norashidah (Recent Trends in Civil Engineering and Built Environment, 2021)
Steel hollow sections are frequently utilised in the building sector because of its structural benefits and ability to save construction time. The steel hollow section, on the other hand, is prone to buckling due to its high slenderness ratio. By introducing the concrete filled in hollow section, it will help to reduce the buckling of the steel section.  Therefore, this study was carried out to determine the strength of lightweight cellular concrete filled steel hollow section added  steel fiber . The dimension of steel hollow section that used is 100 x100 x350 mm with thickness of 2mm and 4mm. Specimen was tested under compression test.The result shows that steel fiber can help to increase the strength of lightweight Cellular concrete filled hollow section. The strength increase is due to the enhancing effect from the addition of fiber.